Introduction to radiometry and photometry - McCluney, Ross (Artech House applied photonics series, 2014)
This second edition of an Artech House classic title describes in detail the relationship between radiometry and photometry. It covers information needed to solve problems in radiation transfer and detection, detectors, measuring instruments, and concepts in colorimetry.